2015
DOI: 10.1038/ncomms7189
|View full text |Cite
|
Sign up to set email alerts
|

Formation of lunar swirls by magnetic field standoff of the solar wind

Abstract: Lunar swirls are high-albedo markings on the Moon that occur in both mare and highland terrains; their origin remains a point of contention. Here, we use data from the Lunar Reconnaissance Orbiter Diviner Lunar Radiometer to support the hypothesis that the swirls are formed as a result of deflection of the solar wind by local magnetic fields. Thermal infrared data from this instrument display an anomaly in the position of the silicate Christiansen Feature consistent with reduced space weathering. These data al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 37 publications
4
62
0
Order By: Relevance
“…This includes, in particular, the origin of the dark lanes of the lunar swirls, in agreement with the spectroscopic observations of lunar surface albedo (Pieters et al 1993;Taylor et al 2001;Blewett et al 2007;Kramer et al 2011aKramer et al , 2011bGlotch et al 2015). The in situ observations from plasma instrumentation on board satellites at altitudes from -10 1000 s km include; magnetic and density pile-up, backflow, narrow electrostatic barrier, solitary and lower-hybrid waves, turbulence spectrum, Whistlers, cavity formation, beams, particle pickup, electron heating, ionslowing, reflection and deflection.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This includes, in particular, the origin of the dark lanes of the lunar swirls, in agreement with the spectroscopic observations of lunar surface albedo (Pieters et al 1993;Taylor et al 2001;Blewett et al 2007;Kramer et al 2011aKramer et al , 2011bGlotch et al 2015). The in situ observations from plasma instrumentation on board satellites at altitudes from -10 1000 s km include; magnetic and density pile-up, backflow, narrow electrostatic barrier, solitary and lower-hybrid waves, turbulence spectrum, Whistlers, cavity formation, beams, particle pickup, electron heating, ionslowing, reflection and deflection.…”
Section: Discussionsupporting
confidence: 67%
“…Persistent reduced proton flux leads to a "lighter" color, while extra enhanced proton flux leads to an even "darker" appearance. The interplay between the two results in "white wisps" interspersed with narrow "dark lanes" (Blewett et al 2007;Richmond & Hood 2008;Kramer et al 2011a;Glotch et al 2015;Harnett & Kramer 2015).…”
Section: Lunar Swirls and Magnetic Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diviner measures radiance from 0.3 to 400 Ī¼m, which can be converted to emissivity to inform us about the bulk silicate mineralogy across the surface of the Moon (Greenhagen et al, ; Paige, Foote, et al, ), as well as the thermophysical properties of the lunar regolith (e.g., Bandfield et al, , ; Elder et al, ; Paige, Siegler, et al, ; Siegler et al, , ; Vasavada et al, ). Diviner has contributed to a better understanding of lunar geology, such as highly silicic features (e.g., Glotch et al, ), crater peak compositions (e.g., Song et al, ), and lunar swirls (e.g., Glotch et al, ) and shown how well Diviner data can complement visible to nearā€infrared data, such as the assessment of lunar crystalline plagioclase (e.g., Donaldson Hanna et al, ), examination of volcanics (e.g., Bennett et al, ), and quantification of olivine content (e.g., Arnold et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…2 The exposure of surfaces to immense heat fluxes in magnetic fusion devices remains one of the most critical issue facing the development of a fully functioning, power-generating device. 3 Finally, the interaction of objects in space, such as planets, artificial satellites, and dust particles, with sparse interplanetary plasma or solar wind provides phenomena such as the homogenization of cosmic dust, 4 spontaneous self-alignment of dust clouds, 5 lunar swirls, 6 and damage-induced limitations to the lifetime of the spacecraft. 7 This list is, of course, by no means exhaustive but it clearly illustrates the extensive occurrence and economic importance of plasma-surface interactions.…”
Section: Introductionmentioning
confidence: 99%